2018
DOI: 10.1002/adbi.201800269
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Photolithography: Patterning Escherichia coli Biofilms with High Spatial Control Using Photocleavable Adhesion Molecules

Abstract: Biofilms are not only a leading cause of chronic infections and biofouling, but they also have a tremendous positive potential in biotechnology for biocatalysis and waste treatment. Biofilms are spatially structured communities of microbes, which exchange chemicals and communicate with each other. By spatially controlling bacterial adhesion to surfaces, and therefore the microstructure of biofilms, a promising method of understanding social interactions between bacteria and designed biofilms is developed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…The concept of cell density-dependent changes in cell behavior and phenotypes by DSFbased quorum sensing might underlie our observed cell density-dependent initiation of filamentous cell morphogenesis and directional cell growth 11,34,64 . In further support to this conjecture, previous observations in X. fastidiosa as well as in other bacteria and human cells have shown that quorum sensing mechanisms are activated upon exceeding a local DSF concentration threshold at regions of high cell densities 37,59,[65][66][67] Consistent with this model, a previous study using a X. fastidiosa…”
Section: Bacterial Density-dependent Cell Communication Regulates Filsupporting
confidence: 75%
See 1 more Smart Citation
“…The concept of cell density-dependent changes in cell behavior and phenotypes by DSFbased quorum sensing might underlie our observed cell density-dependent initiation of filamentous cell morphogenesis and directional cell growth 11,34,64 . In further support to this conjecture, previous observations in X. fastidiosa as well as in other bacteria and human cells have shown that quorum sensing mechanisms are activated upon exceeding a local DSF concentration threshold at regions of high cell densities 37,59,[65][66][67] Consistent with this model, a previous study using a X. fastidiosa…”
Section: Bacterial Density-dependent Cell Communication Regulates Filsupporting
confidence: 75%
“…Selective and controlled spatial arrangement of cells and microcolonies are critical prerequisites for the investigation of dynamic biological phenomena of multicellular systems, such as cell plasticity, motility, morphogenesis, and cell-cell communication [35][36][37] . To this end, diverse approaches for selective cell organization with varying complexity and different surface chemical modifications have been previously developed 10,[37][38][39] . To simplify the approach, we exploited the native ability of X. fastidiosa to bind to specific chemical moieties with high efficacy.…”
Section: High Affinity For Cell Adhesion To Gold Enables Noninvasivementioning
confidence: 99%
“…[29,39,40] Communication and/or synchronized behavior in bacterial communities are conceived as phenomena that mainly depend on the cell density and diversity of the species within the community. [12,31] However, a growing body of evidence suggests a paramount role as well for spatial positioning in bacterial societal behavior. [6–8,23,41,42]…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hynes et al [30] accommodated spatially distinct aggregates of E. coli and Salmonella enterica using a casting-based method and suggested that interactions in this consortium may be influenced by spatial scales. Similarly, Chen et al [31] used photolithography to create patterns in adhesion polymers at a resolution of 10 µm. The patterns were subsequently used for specific anchoring of E. coli at those locations, and the authors then monitored bacterial crosstalk using a reporter gene activated by the high cell concentration in neighboring fronts.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing cell densities enhance bacteria motility [18,50] Inhomogeneous cell density patterns of living and dead cells shape biofilm's wrinkle architecture [58] and EPS production is thickness dependent [60] Light Light drives bulk swarm motility in phototactic bacteria and blue light can slow down cells and lead to local cell accumulation [65,66] Blue light can be used to pattern biofilms in genetically engineered cells or to induce biofilm dispersal through cell hyperpolarization [74][75][76][77]79] Mechanical patterning Geometric confinement induces vortex patterns useful to identify swarming motility [70,71] 3D printing and Menifluidics can direct biofilm growth with submillimetre precision [72,[81][82][83]…”
Section: Both Swarms and Biofilms Form On Surfaces But On Surfaces With Different Mechanical Propertiesmentioning
confidence: 99%